Letter from Georg Bredig to Max Bredig, February 9, 1935 - Bredig, Georg (1935)
Georg Bredig (1868-1944) gives his son, Max Albert Bredig (1902-1977), advice on how to do his taxes.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Taxation